Analects of communication on the impact of divorce on society in Arabic country - Faten Mohammad AlQahtani
Divorce seems to be more socially acceptable nowdays and is also the most common issues in the modern world. With the increse rate of divorce, the pace of emotional instability and crime rate is also quicening. Its effect on the family life, interference in the development of the children an crime is obvious.